Indian General Insurance Industry And Its Scope In International Market (International Journal of Innovative Research in Engineering & Management, 2021)
General Insurance is typically defined as any insurance that is not  determined to be life insurance but “General Insurance comprises  of insurance of property against fire, burglary etc and personal  insurance such as Accident and Health Insurance and liability  insurance which covers legal liabilities”[1]. “There are also other  covers such as Errors and Omissions insurance for professionals,  credit insurance” [1]. “General Insurance acts as aegis to the  financial causalities and alongside it also acts an economical  back-up for a nation’s economy” [2].Insurance allied up with  banking sector dispenses up to 7% of India’s total GDP. Till date  we have observed foreign insurance companies engaging into  Indian markets and having share of 24% of FDI being allowed in  the Indian market.
Keywords: Foreign insurance; Risk; IRDA; Micro-insurance; Macro insurance